How to link pyrene to its host lipid to minimize the extent of membrane perturbations and to optimize pyrene dimer formation - Fraňová, Miroslava Dékány; Repáková, Jarmila; Holopainen, Juha M; Vattulainen, Ilpo (Chemistry and physics of lipids, 2014)
We study how lipid probes based on pyrene-labeling could be designed to minimize perturbations in lipid bilayers, and how the same design principles could be exploited to develop probes which gauge lipid dynamics primarily within a single lipid monolayer or between them. To this end, we use atomistic molecular dynamics simulations to consider membranes where pyrene moieties are attached to lipid acyl chains in varying positions. We find that in a DOPC bilayer the conformational ordering of lipids around di-pyrenyl-PC probes is altered to a largely similar extent regardless of where the pyrene moiety is attached to the hydrocarbon chain. This is in contrast to saturated membranes, where pyrene-induced perturbations have been observed to be more prominent. Meanwhile, the formation of pyrene dimers depends on the linkage point between pyrene and its host lipid. Membrane-spanning dimers between lipids in different membrane leaflets are observed only if the pyrene moiety is attached to the latter half of the acyl chain. A seemingly minor change to link pyrene to an acyl chain that is two carbons shorter leads to a situation where membrane-spanning dimers are no longer observed. Further, simulations suggest that formation of dimers is a slow process, where the rate is limited by both lateral diffusion and the dimerization process once the two probes are neighbors to one another. Typical lifetimes of pyrene dimers turn out be of the order of nanoseconds. The results are expected to pave the way for designing ways to consider experimentally topics such as intraleaflet lateral diffusion, motion of lipids within and between membrane domains, and membrane domain registration across bilayers.
Keywords: lipidové dvojvrstvy; Cell Membrane; Lipid Bilayers; fluorescenční barviva; Pyrenes; Time Factors; Membrane Lipids; pyreny; časové faktory; Dimerization; Fluorescent Dyes; dimerizace; Hydrocarbons; buněčná membrána; membránové lipidy; uhlovodíky